Effects of Soybean Oil Modified Cellulose Fibril and Organosilane Modified Cellulose Fibril on Crystallization of Polypropylene - Sarit Thanomchat; Kawee Srikulkit (Advances in Materials Science and Engineering)
Soybean oil modified cellulose fibril (Oil-g-CF) and organosilane modified cellulose fibril (Silane-g-CF) were prepared using maleinized soybean oil and hexadecyltrimethoxysilane, respectively. Thus obtained modified cellulose fibril was added to polypropylene by a simple melt mixing on a hotplate. PP/modified CF composites with 4.0 wt% filler content were prepared. The composites were subject to a polarized optical microscope to investigate particle dispersion, supramolecular morphology, and crystallization behavior. It was found that Silane-g-CF exhibited smaller particle sizes with better particle distribution when compared to Oil-g-CF. In addition, the etched composite samples unveiled an increase in a number of spherulite crystals as well as a decrease in the spherulite size. The nonisothermal crystallization study of composites revealed that both Oil-g-CF and Silane-g-CF were capable of nucleating PP by facilitating faster crystallization process and raising the number of spherulites. The DSC results indicated that Silane-g-CF was able to perform a more effective nucleation than Oil-g-CF, judged by a higher crystallization temperature. Moreover, PP composites containing Oil-g-CF and Silane-g-CF had higher crystallinity by 7% and 10%, for the first and the latter, respectively, when compared to neat PP.